Agricultural Intelligence Decision System Using Big Data Analysis - Patil, Harshitha P; D, Gokul; M, Dharmatej; Reddy, K V Rajashekhar; BR, Chandan Raj (International Journal of Computer Sciences and Engineering, 2025)
Using hadoop in big data technologies into agriculture presents a significant challenge; at the same time, this technology contributes effectively in many countries’ economic and social development. In this work, we will study environmental data provided by precision agriculture information technologies, which represents a crucial source of data in need of being wisely managed and analyzed with appropriate methods and tools in order to extract the meaningful information by providing decision making support to the farmers.